Magnetic flux inversion in a peculiar changing look AGN. Issue 1 (9th January 2021) - Scepi, Nicolas; Begelman, Mitchell C; Dexter, Jason
ABSTRACT: We argue that the changing-look event in the active galactic nucleus (AGN) 1ES 1927+654, followed by a dip of three orders of magnitude in the X-ray luminosity, is controlled by a change in the accretion rate and an inversion of magnetic flux in a magnetically arrested disc (MAD). Before the changing-look event, strong magnetic flux on the black hole powers X-ray emission via the Blandford–Znajek process, while the UV emission is produced by a radiatively inefflcient magnetized disc. An advection event, bringing flux of the opposite polarity, propagates inward leading, first, to a rise in the UV/optical luminosity and, then, to a dip in the X-ray luminosity. We find that the observed time-scale between the beginning of the changing-look event and the minimum in the X-ray luminosity, ≈200 d, is in agreement with the time needed to cancel the magnetic flux in a MAD extending to ≈180 rg . Although flux inversion events might be rare due to the large ratio of flux-to-mass that is needed, we argue that AGN showing an unusually high ratio of X-ray to UV luminosity are prime candidates for such events. We suggest that similar events may lead to jet interruptions in radio-loud objects.